Preparation process of 2, 3, 4-trihydroxy benzaldehyde
Through modified nanoporous zeolite catalyst and magnetic field-assisted microwave radiation technology, the complex problem of wastewater treatment in traditional preparation processes is solved, and efficient and environmentally friendly preparation of 2,3,4-trihydroxybenzaldehyde with high yield and safety sex.
Patent Information
- Application Number
- CN202411437005.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2025-01-03
AI Technical Summary
The use of aluminum trichloride catalysts in the traditional 2,3,4-trihydroxybenzaldehyde preparation process leads to the generation of large amounts of aluminum-containing wastewater, which is complex and not environmentally friendly, and lacks high yield and safe preparation technology.
The modified nanoporous zeolite catalyst was used to prepare by loading nickel ferrite and bismuth trifluoromethanesulfonate, combined with magnetic field-assisted microwave radiation technology, and formic acid was used as the formylation reagent and phthalol as raw materials to control the reaction conditions. Improve catalytic effect.
A high yield, safe and environmentally friendly preparation process is achieved, the catalyst is easy to recover, and no polluting wastewater is produced, the reaction yield is high, the selectivity is good, the reaction time is short, and the energy consumption is low.
Smart Images

Figure BDA0005085305410000081
Abstract
Description
Technical Field
[0001] The invention relates to the field of pharmaceutical intermediate synthesis, in particular to a preparation process of 2,3,4-trihydroxybenzaldehyde. Background Art
[0002] Parkinson's disease is a chronic degenerative disorder of the central nervous system that impairs the patient's motor skills, language ability and other functions. Dopamine is needed in the brain to direct muscle activity, and a lack of sufficient dopamine will cause various activity disorders. Currently, the most commonly used drug for the treatment of Parkinson's disease is levodopa, with the trade name Madopar. Madopar is a compound preparation made of levodopamine and the peripheral decarboxylase inhibitor benserazide hydrochloride in a ratio of 4:1. 2,3,4-trihydroxybenzaldehyde is the key intermediate for the preparation of benserazide hydrochloride.
[0003] 2,3,4-Trihydroxybenzaldehyde is a white crystal with a melting point of 158°C and a molecular formula of C7H6O 4, It is also a phenolic benzaldehyde with antibacterial activity. The traditional preparation process mostly uses aluminum chloride as a catalyst, which will produce a large amount of aluminum-containing wastewater and the subsequent treatment process is complicated. Therefore, it is of great significance to develop a high-yield, safe and environmentally friendly preparation technology. Summary of the invention
[0004] The object of the present invention is to provide a preparation process of 2,3,4-trihydroxybenzaldehyde to solve the problems existing in the prior art.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: a preparation process of 2,3,4-trihydroxybenzaldehyde, wherein the preparation process of 2,3,4-trihydroxybenzaldehyde uses modified nanoporous zeolite as a catalyst, pyrogallol as a raw material, and formic acid as a formylation agent, and an auxiliary process is applied during the preparation process.
[0006] Furthermore, the modified nanoporous zeolite is prepared by loading nickel ferrite and bismuth trifluoromethanesulfonate on nanoporous zeolite.
[0007] Furthermore, the auxiliary process is a magnetic field-assisted microwave radiation technology.
[0008] Further, the method comprises the following preparation steps:
[0009] (1) placing the nanoporous zeolite in a 4-10 wt % hydrochloric acid aqueous solution, dispersing it with 30-40 kHz ultrasonic wave for 30-60 min, soaking it for 10-15 h, adding a NaOH solution dropwise until it becomes neutral, filtering out the solid, washing it with deionized water for 2-3 times, and drying it at 80° C. for 6-8 h to obtain the activated nanoporous zeolite;
[0010] (2) dissolving ferric nitrate nonahydrate and nickel nitrate hexahydrate in deionized water to obtain a mixed solution, wherein the concentration of iron ions is 0.5-0.6 mol / L and the concentration of nickel ions is 0.25-0.30 mol / L, adding activated nanoporous zeolite in an amount of 0.8-1.2 times the mass of the mixed solution, adding anhydrous citric acid in a molar ratio of 0.5-1.0 times the mass of the metal ions to the mixed solution, stirring at 300-400 r / min for 1-2 h, continuing to add 25-28 wt % ammonia water to adjust the pH to 7.0-8.0, evaporating at 60-70° C. for 2-3 h, placing in a vacuum drying oven at 105° C. and 50 kPa for 12 h, heating to 800° C. at 10° C. / min in a muffle furnace, and calcining for 2 h to obtain a nanoporous zeolite catalyst loaded with nickel ferrite;
[0011] (3) 2.0-3.0 g of nanoporous zeolite loaded with nickel ferrite is placed in a container, 10-15 mL of ethanol solution of bismuth trifluoromethanesulfonate is added dropwise under magnetic stirring at 400-500 r / min, and the mixture is reacted at 50-60° C. for 10-12 h under nitrogen protection. After cooling the reaction to room temperature, the obtained mixture is filtered, and the filter cake is placed in a vacuum drying oven at 70° C. and 50 kPa for 12-16 h to finally obtain a modified nanoporous zeolite catalyst:
[0012] (4) adding ethyl acetate, modified nanoporous zeolite catalyst, formic acid, and pyrogallol into the reaction kettle in sequence, with the material ratio being 10-12:3-5:2.6-3.1:1, controlling the reaction temperature to be -10-0°C, stirring at 400-600 r / min for 30-45 min to obtain a mixed solution, placing the mixed solution under a magnetron to receive microwave radiation for 3-5 min, and applying a magnetic field to obtain a precursor solution;
[0013] (5) Add 3 mol / L hydrochloric acid in an amount of 1 to 1.2 times the mass of ethyl acetate to the precursor solution, remove the ethyl acetate by distillation under reduced pressure, add isopropanol in an amount of 0.5 to 0.6 times the mass of pyrogallol, heat to 65 to 68° C. in an oil bath, stir at 300 to 400 r / min for 15 to 20 min, cool to −5 to 0° C. in an ice bath for 2.5 to 3.0 h, filter to obtain a solid, and dry under reduced pressure to obtain 2,3,4-trihydroxybenzaldehyde.
[0014] Furthermore, in step (1), the particle size of the nanoporous zeolite is 100-200 nm.
[0015] Furthermore, the metal ions in step (2) refer to the sum of iron ions and nickel ions.
[0016] Furthermore, the bismuth trifluoromethanesulfonate solution in step (3) is prepared by dissolving bismuth trifluoromethanesulfonate in an ethanol solution to obtain an ethanol solution of bismuth trifluoromethanesulfonate having a concentration of 100 to 120 g / L.
[0017] Furthermore, the process conditions of microwave radiation in step (4) are that the microwave frequency is 2450 MHz and the output power is 100%.
[0018] Furthermore, in step (4), the magnetic field strength is 0.5-0.6T.
[0019] Furthermore, the process conditions for reduced pressure drying in step (4) are a vacuum degree of 1.6 to 1.8 kPa, a temperature of 50 to 55° C., and a drying time of 10 to 15 hours.
[0020] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0021] The invention prepares a nanoporous zeolite catalyst loaded with nickel ferrite and bismuth trifluoromethanesulfonate, takes pyrogallol as a raw material, and formic acid as a formylation agent, and applies a magnetic field-assisted microwave radiation technology during the preparation process. The preparation process has the advantages of high yield, safety and environmental protection.
[0022] Firstly, a nanoporous zeolite loaded with nickel ferrite and bismuth trifluoromethanesulfonate is prepared as a catalyst, nickel ferrite is deposited on the nanoporous zeolite by a sol-gel method, and bismuth trifluoromethanesulfonate is also deposited in the nanoporous zeolite by an impregnation method. The catalyst does not require an oxygen-free environment, and the catalyst is easy to recover after use, and no polluting wastewater is generated. Secondly, a magnetic field-assisted microwave radiation technology is applied during the preparation process of the preparation process. Microwave radiation provides a powerful means for organic synthesis, which can improve the catalytic effect of the nanoporous zeolite catalyst, increase the number of acidic catalytic sites in the nanoporous zeolite cavities, and make the reaction yield high, the selectivity good, and the reaction time short. The application of a magnetic field can affect the molecular arrangement and energy state of the reactants, thereby changing the reaction path and rate. Because the nickel ferrite loaded on the nanoporous zeolite is a magnetic substance, the application of a magnetic field can further excite the catalytic activity of the nickel ferrite. When combined with microwave radiation, the magnetic field can further optimize the reaction conditions, improve the purity and yield of the product, and reduce energy consumption. Therefore, the preparation process has the advantages of high yield, safety and environmental protection. DETAILED DESCRIPTION
[0023] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0024] Example 1
[0025] A preparation process of 2,3,4-trihydroxybenzaldehyde comprises the following preparation steps:
[0026] (1) placing a nanoporous zeolite with a particle size of 100 nm in a 4 wt % hydrochloric acid aqueous solution, dispersing it with 30 kHz ultrasonic wave for 30 min, soaking it for 10 h, adding a NaOH solution dropwise until it becomes neutral, filtering out the solid, washing it twice with deionized water, and drying it at 80° C. for 6 h to obtain the activated nanoporous zeolite;
[0027] (2) dissolving ferric nitrate nonahydrate and nickel nitrate hexahydrate in deionized water to obtain a mixed solution, wherein the concentration of iron ions is 0.5 mol / L and the concentration of nickel ions is 0.25 mol / L, adding activated nanoporous zeolite in an amount 0.8 times the mass of the mixed solution, adding anhydrous citric acid in an amount 0.5 times the molar ratio of the metal ions to the mixed solution, wherein the metal ions refer to the sum of iron ions and nickel ions, stirring at 300 r / min for 1 hour, continuing to add 25 wt % ammonia water to adjust the pH to 7.0, evaporating at 60° C. for 2 hours, placing in a vacuum drying oven at 105° C. and 50 kPa for 12 hours, heating to 800° C. at 10° C. / min in a muffle furnace, and calcining for 2 hours to obtain a nanoporous zeolite catalyst loaded with nickel ferrite;
[0028] (3) dissolving bismuth trifluoromethanesulfonate in an ethanol solution to prepare an ethanol solution of bismuth trifluoromethanesulfonate having a concentration of 100 / L;
[0029] (4) 2.0 g of nanoporous zeolite loaded with nickel ferrite was placed in a container, 10 mL of ethanol solution of bismuth trifluoromethanesulfonate was added dropwise under magnetic stirring at 400 r / min, and the mixture was reacted at 50° C. for 10 h under nitrogen protection. After cooling the reaction to room temperature, the obtained mixture was filtered, and the filter cake was placed in a vacuum drying oven at 70° C. and 50 kPa for 12 h to finally obtain a modified nanoporous zeolite catalyst;
[0030] (5) Ethyl acetate, modified nanoporous zeolite catalyst, formic acid, and pyrogallol were added into the reaction kettle in sequence, with the material ratio being 10:3:2.6:1, the reaction temperature was controlled to be -10°C, and the mixture was stirred at 400 r / min for 30 min to obtain a mixed solution, and the mixed solution was placed under a magnetron to receive microwave radiation for 3 min, with a microwave frequency of 2450 MHz and an output power of 100%, and a magnetic field was applied with a magnetic field strength of 0.5 T to obtain a precursor solution;
[0031] (6) Add 3 mol / L hydrochloric acid with a mass of 1 times that of ethyl acetate to the precursor solution, remove the ethyl acetate by vacuum distillation, add isopropanol with a mass of 0.5 times that of pyrogallol, heat to 65°C in an oil bath, stir at 300 r / min for 15 min, cool to -5°C and ice bath for 2.5 h, filter to obtain a solid, and dry under reduced pressure at a vacuum degree of 1.6 kPa, a temperature of 50°C, and a drying time of 10 h to obtain 2,3,4-trihydroxybenzaldehyde.
[0032] Example 2
[0033] A preparation process of 2,3,4-trihydroxybenzaldehyde comprises the following preparation steps:
[0034] (1) placing a nanoporous zeolite with a particle size of 150 nm in a 7 wt % hydrochloric acid aqueous solution, dispersing it with 35 kHz ultrasonic wave for 45 min, soaking it for 13 h, adding a NaOH solution dropwise until it becomes neutral, filtering out the solid, washing it twice with deionized water, and drying it at 80° C. for 7 h to obtain the activated nanoporous zeolite;
[0035] (2) dissolving ferric nitrate nonahydrate and nickel nitrate hexahydrate in deionized water to obtain a mixed solution, wherein the concentration of iron ions is 0.55 mol / L and the concentration of nickel ions is 0.28 mol / L, adding activated nanoporous zeolite in an amount 1.0 times the mass of the mixed solution, adding anhydrous citric acid in an amount 0.8 times the molar ratio of the metal ions to the mixed solution, wherein the metal ions refer to the sum of the iron ions and the nickel ions, stirring at 350 r / min for 1.5 h, continuing to add 27 wt % ammonia water to adjust the pH to 7.5, evaporating at 65° C. for 2.5 h, placing in a vacuum drying oven at 105° C. and 50 kPa for 12 h, heating to 800° C. at 10° C. / min in a muffle furnace, and calcining for 2 h to obtain a nanoporous zeolite catalyst loaded with nickel ferrite;
[0036] (3) dissolving bismuth trifluoromethanesulfonate in an ethanol solution to prepare an ethanol solution of bismuth trifluoromethanesulfonate having a concentration of 110 g / L;
[0037] (4) 2.5 g of nanoporous zeolite loaded with nickel ferrite was placed in a container, 13 mL of ethanol solution of bismuth trifluoromethanesulfonate was added dropwise under magnetic stirring at 450 r / min, and the mixture was reacted at 55° C. for 11 h under nitrogen protection. After cooling the reaction to room temperature, the obtained mixture was filtered, and the filter cake was placed in a vacuum drying oven at 70° C. and 50 kPa for 14 h to finally obtain a modified nanoporous zeolite catalyst;
[0038] (5) Ethyl acetate, modified nanoporous zeolite catalyst, formic acid, and pyrogallol were added to the reaction kettle in sequence, with a material ratio of 11:4:2.9:1, the reaction temperature was controlled to be -5°C, and the mixture was stirred at 500 r / min for 38 min to obtain a mixed solution, and the mixed solution was placed under a magnetron to receive microwave radiation for 4 min, with a microwave frequency of 2450 MHz and an output power of 100%, and a magnetic field was applied with a magnetic field strength of 0.6 T to obtain a precursor solution;
[0039] (6) Add 3 mol / L hydrochloric acid (1.1 times the mass of ethyl acetate) to the precursor solution, remove the ethyl acetate by vacuum distillation, add isopropanol (0.5 times the mass of pyrogallol), heat to 66°C in an oil bath, stir at 350 r / min for 18 min, cool to -3°C and ice bath for 2.8 h, filter to obtain a solid, and dry under reduced pressure at a vacuum degree of 1.7 kPa, a temperature of 53°C, and a drying time of 13 h to obtain 2,3,4-trihydroxybenzaldehyde.
[0040] Example 3
[0041] A preparation process of 2,3,4-trihydroxybenzaldehyde comprises the following preparation steps:
[0042] (1) placing a nanoporous zeolite with a particle size of 200 nm in a 10 wt % hydrochloric acid aqueous solution, dispersing it by ultrasonic at 40 kHz for 60 min, soaking it for 15 h, dropping a NaOH solution until it is neutral, filtering out the solid, washing it with deionized water three times, and drying it at 80° C. for 8 h to obtain the activated nanoporous zeolite;
[0043] (2) dissolving ferric nitrate nonahydrate and nickel nitrate hexahydrate in deionized water to obtain a mixed solution, wherein the concentration of iron ions is 0.6 mol / L and the concentration of nickel ions is 0.30 mol / L, adding activated nanoporous zeolite in an amount 1.2 times the mass of the mixed solution, adding anhydrous citric acid in an amount 1.0 times the molar ratio of the metal ions to the mixed solution, wherein the metal ions refer to the sum of the iron ions and the nickel ions, stirring at 400 r / min for 2 h, continuing to add 28 wt % ammonia water to adjust the pH to 8.0, evaporating at 70° C. for 3 h, placing in a vacuum drying oven at 105° C. and 50 kPa for 12 h, heating to 800° C. at 10° C. / min in a muffle furnace, and calcining for 2 h to obtain a nanoporous zeolite catalyst loaded with nickel ferrite;
[0044] (3) dissolving bismuth trifluoromethanesulfonate in an ethanol solution to prepare an ethanol solution of bismuth trifluoromethanesulfonate having a concentration of 120 g / L;
[0045] (4) 3.0 g of nanoporous zeolite loaded with nickel ferrite was placed in a container, 15 mL of ethanol solution of bismuth trifluoromethanesulfonate was added dropwise under magnetic stirring at 500 r / min, and the mixture was reacted at 60° C. for 12 h under nitrogen protection. After cooling the reaction to room temperature, the obtained mixture was filtered, and the filter cake was placed in a vacuum drying oven at 70° C. and 50 kPa for 16 h to finally obtain a modified nanoporous zeolite catalyst;
[0046] (5) Ethyl acetate, modified nanoporous zeolite catalyst, formic acid, and pyrogallol were added into the reaction kettle in sequence, with the material ratio being 12:5:3.1:1, the reaction temperature was controlled to be 0°C, and the mixture was stirred at 500 r / min for 38 min to obtain a mixed solution, and the mixed solution was placed under a magnetron to receive microwave radiation for 4 min, with a microwave frequency of 2450 MHz and an output power of 100%, and a magnetic field was applied with a magnetic field strength of 0.6 T to obtain a precursor solution;
[0047] (6) Add 3 mol / L hydrochloric acid (1.2 times the mass of ethyl acetate) to the precursor solution, remove the ethyl acetate by vacuum distillation, add isopropanol (0.6 times the mass of pyrogallol), heat to 68°C in an oil bath, stir at 400 r / min for 20 min, cool to 0°C in an ice bath for 3.0 h, filter to obtain a solid, and dry under reduced pressure at a vacuum degree of 1.8 kPa, a temperature of 55°C, and a drying time of 15 h to obtain 2,3,4-trihydroxybenzaldehyde.
[0048] Comparative Example 1
[0049] The difference between Comparative Example 1 and Example 2 is that there is no step (1), and step (2) is changed to: dissolving ferric nitrate nonahydrate and nickel nitrate hexahydrate in deionized water to obtain a mixed solution, wherein the concentration of iron ions is 0.55 mol / L and the concentration of nickel ions is 0.28 mol / L, adding 1.0 times the mass of the mixed solution of nanoporous zeolite, adding anhydrous citric acid to the mixed solution at a molar ratio of 0.8 times the metal ions, wherein the metal ions refer to the sum of iron ions and nickel ions, stirring at 350 r / min for 1.5 h, continuing to add 27 wt % ammonia water to adjust the pH to 7.5, evaporating at 65° C. for 2.5 h, placing in a vacuum drying oven at 105° C. and 50 kPa for 12 h, heating to 800° C. at 10° C. / min in a muffle furnace, and calcining for 2 h to obtain a nanoporous zeolite catalyst loaded with nickel ferrite; the remaining steps are the same as those of Example 2.
[0050] Comparative Example 2
[0051] The difference between Comparative Example 2 and Example 2 is that there is no step (2), and step (4) is changed to: 2.5 g of activated nanoporous zeolite is placed in a container, 13 mL of ethanol solution of bismuth trifluoromethanesulfonate is added dropwise under magnetic stirring at 450 r / min, and the reaction is carried out at 55° C. for 11 h under nitrogen protection. After cooling the reaction to room temperature, the obtained mixture is filtered, and the filter cake is placed in a vacuum drying oven at 70° C. and 50 kPa for 14 h to finally obtain a nanoporous zeolite catalyst loaded with bismuth trifluoromethanesulfonate; the remaining steps are the same as those in Example 2.
[0052] Comparative Example 3
[0053] The difference between Comparative Example 3 and Example 2 is that there are no steps (3) and (4), and step (2) is changed to: dissolving ferric nitrate nonahydrate and nickel nitrate hexahydrate in deionized water to obtain a mixed solution, wherein the concentration of iron ions is 0.55 mol / L and the concentration of nickel ions is 0.28 mol / L, adding 1.0 times the mass of the mixed solution of activated nanoporous zeolite, adding anhydrous citric acid to the mixed solution at a molar ratio of 0.8 times the metal ions, wherein the metal ions refer to the sum of iron ions and nickel ions, stirring at 350 r / min for 1.5 h, continuing to add 27 wt % ammonia water to adjust the pH to 7.5, evaporating at 65 ° C for 2.5 h, placing in a vacuum drying oven at 105 ° C, 50 kPa for 12 h, heating to 800 ° C in a muffle furnace at 10 ° C / min, calcining for 2 h to obtain a modified nanoporous zeolite catalyst; the remaining steps are the same as Example 2.
[0054] Comparative Example 4
[0055] The difference between Comparative Example 4 and Example 2 is that step (5) is different. Step (5) is changed to: ethyl acetate, modified nanoporous zeolite catalyst, formic acid, and pyrogallol are added to the reactor in sequence, and the material ratio is 11:4:2.9:1. The reaction temperature is controlled to be -5°C, and the mixture is stirred at 500 r / min for 38 min to obtain a mixed solution. The mixed solution is placed under a magnetron and subjected to microwave radiation for 4 min. The microwave frequency is 2450 MHz and the output power is 100% to obtain a precursor solution. The remaining steps are the same as Example 2.
[0056] Comparative Example 5
[0057] The difference between Comparative Example 5 and Example 2 is that step (5) is different. Step (5) is changed to: ethyl acetate, modified nanoporous zeolite catalyst, formic acid, and pyrogallol are added to the reaction kettle in sequence, and the material ratio is 11:4:2.9:1. The reaction temperature is controlled to be -5°C, and the mixture is stirred at 500 r / min for 38 min to obtain a mixed solution, and a magnetic field is applied with a magnetic field strength of 0.6 T to obtain a precursor solution. The remaining steps are the same as Example 2.
[0058] Comparative Example 6
[0059] The difference between Comparative Example 6 and Example 2 is that step (5) is different. Step (5) is changed to: ethyl acetate, modified nanoporous zeolite catalyst, formic acid, and pyrogallol are added to the reactor in sequence, with a material ratio of 11:4:2.9:1, the reaction temperature is controlled to -5°C, and stirred at 500r / min for 38min to obtain a precursor solution; the remaining steps are the same as Example 2.
[0060] Comparative Example 7
[0061] The difference between Comparative Example 7 and Example 2 is that there are no steps (1) to (4), and step (5) is changed to: ethyl acetate, aluminum chloride, formic acid, and pyrogallol are added to the reaction kettle in sequence, and the material ratio is 11:4:2.9:1, the reaction temperature is controlled to -5°C, and stirred at 500 r / min for 60 min to obtain a mixed solution, and the mixed solution is placed under a magnetron to receive microwave radiation for 4 min, the microwave frequency is 2450 MHz, the output power is 100%, and a magnetic field is applied with a magnetic field strength of 0.6 T to obtain a precursor solution; the remaining steps are the same as Example 2.
[0062] Comparative Example 8
[0063] The difference between Comparative Example 8 and Example 2 is that there are no steps (1) to (4), and step (5) is changed to: ethyl acetate, aluminum chloride, triethyl orthoformate, and pyrogallol are added to the reaction kettle in sequence, and the material ratio is 11:4:2.9:1, the reaction temperature is controlled to -5°C, and stirred at 500r / min for 60min to obtain a mixed solution, and the mixed solution is placed under a magnetron to receive microwave radiation for 4min, the microwave frequency is 2450MHz, the output power is 100%, and a magnetic field is applied with a magnetic field strength of 0.6T to obtain a precursor solution; the remaining steps are the same as Example 2.
[0064] Effect example
[0065] The following Table 1 provides a summary of the synthesis of 2,3,4-trihydroxybenzaldehyde prepared using the preparation processes of Examples 1 to 3 of the present invention and Comparative Examples 1 to 8.
[0066] Table 1
[0067]
[0068] From the data comparison of the synthesis summary of the embodiment and the comparative example, it can be found that the present invention prepares a nanoporous zeolite loaded with nickel ferrite and bismuth trifluoromethanesulfonate as a catalyst, the nickel ferrite is deposited on the nanoporous zeolite by a sol-gel method, and the bismuth trifluoromethanesulfonate is also deposited in the nanoporous zeolite by an impregnation method. The catalyst does not require an oxygen-free environment, and the catalyst is easy to recover after use, and no polluting wastewater is generated; secondly, the magnetic field-assisted microwave radiation technology is applied during the preparation process of the present preparation process, and microwave radiation provides a powerful means for organic synthesis, which can improve the nanoporous zeolite. The catalytic effect of the porous zeolite catalyst increases the number of acidic catalytic sites in the cavities of the nanoporous zeolite, resulting in a high reaction yield, good selectivity and a short reaction time. The application of a magnetic field can affect the molecular arrangement and energy state of the reactants, thereby changing the reaction path and rate. Because the nickel ferrite loaded on the nanoporous zeolite is a magnetic substance, the application of a magnetic field will further stimulate the catalytic activity of the nickel ferrite. When combined with microwave radiation, the magnetic field can further optimize the reaction conditions, improve the purity and yield of the product and reduce energy consumption. Therefore, this preparation process has the advantages of high yield, safety and environmental protection.
[0069] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A process for preparing 2,3,4-trihydroxybenzaldehyde, characterized in that: The preparation process of 2,3,4-trihydroxybenzaldehyde uses modified nanoporous zeolite as a catalyst, pyrogallol as a raw material, and formic acid as a formylation agent, and an auxiliary process is applied during the preparation process.
2. A process for preparing 2,3,4-trihydroxybenzaldehyde according to claim 1, characterized in that: The modified nanoporous zeolite is prepared by loading nickel ferrite and bismuth trifluoromethanesulfonate on nanoporous zeolite.
3. A process for preparing 2,3,4-trihydroxybenzaldehyde according to claim 2, characterized in that: The auxiliary process is a magnetic field-assisted microwave radiation technology.
4. A process for preparing 2,3,4-trihydroxybenzaldehyde according to claim 1, characterized in that: The method comprises the following preparation steps: (1) placing the nanoporous zeolite in a 4-10 wt % hydrochloric acid aqueous solution, dispersing it with 30-40 kHz ultrasonic wave for 30-60 min, soaking it for 10-15 h, adding a NaOH solution dropwise until it becomes neutral, filtering out the solid, washing it with deionized water for 2-3 times, and drying it at 80° C. for 6-8 h to obtain the activated nanoporous zeolite; (2) dissolving ferric nitrate nonahydrate and nickel nitrate hexahydrate in deionized water to obtain a mixed solution, wherein the concentration of iron ions is 0.5-0.6 mol / L and the concentration of nickel ions is 0.25-0.30 mol / L, adding activated nanoporous zeolite in an amount of 0.8-1.2 times the mass of the mixed solution, adding anhydrous citric acid in a molar ratio of 0.5-1.0 times the mass of the metal ions to the mixed solution, stirring at 300-400 r / min for 1-2 h, continuing to add 25-28 wt % ammonia water to adjust the pH to 7.0-8.0, evaporating at 60-70° C. for 2-3 h, placing in a vacuum drying oven at 105° C. and 50 kPa for 12 h, heating to 800° C. at 10° C. / min in a muffle furnace, and calcining for 2 h to obtain a nanoporous zeolite catalyst loaded with nickel ferrite; (3) placing 2.0-3.0 g of a nanoporous zeolite loaded with nickel ferrite in a container, adding 10-15 mL of an ethanol solution of bismuth trifluoromethanesulfonate dropwise under magnetic stirring at 400-500 r / min, reacting at 50-60° C. for 10-12 h under nitrogen protection, cooling the reaction to room temperature, filtering the resulting mixture, and drying the filter cake in a vacuum drying oven at 70° C. and 50 kPa for 12-16 h to finally obtain a modified nanoporous zeolite catalyst; (4) adding ethyl acetate, modified nanoporous zeolite catalyst, formic acid, and pyrogallol into the reaction kettle in sequence, with the material ratio being 10-12:3-5:2.6-3.1:1, controlling the reaction temperature to be -10-0°C, stirring at 400-600 r / min for 30-45 min to obtain a mixed solution, placing the mixed solution under a magnetron to receive microwave radiation for 3-5 min, and applying a magnetic field to obtain a precursor solution; (5) Add 3 mol / L hydrochloric acid in an amount of 1 to 1.2 times the mass of ethyl acetate to the precursor solution, remove the ethyl acetate by distillation under reduced pressure, add isopropanol in an amount of 0.5 to 0.6 times the mass of pyrogallol, heat to 65 to 68° C. in an oil bath, stir at 300 to 400 r / min for 15 to 20 min, cool to −5 to 0° C. in an ice bath for 2.5 to 3.0 h, filter to obtain a solid, and dry under reduced pressure to obtain 2,3,4-trihydroxybenzaldehyde.
5. A process for preparing 2,3,4-trihydroxybenzaldehyde according to claim 4, characterized in that: The particle size of the nanoporous zeolite in step (1) is 100-200 nm.
6. A process for preparing 2,3,4-trihydroxybenzaldehyde according to claim 4, characterized in that: The metal ions in step (2) refer to the sum of iron ions and nickel ions.
7. A process for preparing 2,3,4-trihydroxybenzaldehyde according to claim 4, characterized in that: The bismuth trifluoromethanesulfonate solution in step (3) is prepared by dissolving bismuth trifluoromethanesulfonate in an ethanol solution to obtain an ethanol solution of bismuth trifluoromethanesulfonate having a concentration of 100 to 120 g / L.
8. A process for preparing 2,3,4-trihydroxybenzaldehyde according to claim 4, characterized in that: The process conditions of microwave radiation in step (4) are as follows: microwave frequency is 2450 MHz and output power is 100%.
9. A process for preparing 2,3,4-trihydroxybenzaldehyde according to claim 4, characterized in that: In the step (4), the magnetic field strength is 0.5-0.6T.
10. A process for preparing 2,3,4-trihydroxybenzaldehyde according to claim 4, characterized in that: The process conditions for reduced pressure drying in step (4) are as follows: vacuum degree of 1.6-1.8 kPa, temperature of 50-55° C., and drying time of 10-15 h.
